Seroadaptive Strategies of Vancouver Gay and Bisexual Men in a Treatment as Prevention Environment. Issue 4 (21st March 2018) - Roth, Eric Abella; Cui, Zishan; Rich, Ashleigh; Lachowsky, Nathan; Sereda, Paul; Card, Kiffer George; Jollimore, Jody; Howard, Terry; Armstrong, Heather; Moore, David; Hogg, Robert
ABSTRACT: British Columbia's treatment as prevention policy has provided free access to highly active antiretroviral therapy (HAART) to all HIV-positive provincial residents since 1996. One outcome is an increase in HIV-positive gay and bisexual men (GBM) with suppressed viral loads. Previous cross-sectional analyses indicated that some Vancouver GBM now recognize condomless anal sex with men on HAART who report a suppressed viral load as a seroadaptive strategy. To test the hypothesis that this new strategy, termed viral load sorting (VLS), is recognized and used among by GBM in the Momentum Health Study, we analyzed longitudinal data for HIV-negative/unknown ( n  = 556) and HIV-positive ( n  = 218) serostatus participants. Analyses indicated that both groups reported VLS, and that serostatus and Treatment Optimism Scale scores were significant determinants in frequency and use. Results exemplify the medicalization of sex and Rogers' Diffusion Of Preventative Innovations Model, and they have important implications for HIV research and GBM sexual decision-making.